Student Dropout in Vocational High School from the Point of View of Service-Dominant Logic: A Theoretical Essay (Global Journal of Management and Business Research, 2023)
This theoretical essay analyzes the phenomenon of student dropout in vocational high school, based on the premises of Service Dominant Logic. This theoretical body was used to approach the relationships between the individual, institutional and social causes that lead to drop out. Focusing on the concepts of integration (or disintegration) of resources and cocreation (or co-destruction) of value, a review of the different causes that lead to dropout is made. Then, an analytical-reflexive analysis is carried out, articulating the causes of drop out, the typology of factors that hinder the integration of resources, and the proposals for confrontation raised in the literature. The results show that the causes can be classified into personal, social and pedagogical/school issues, and simultaneous actions are needed to face them, coordinated by an institutional logic that allows the social inclusion of students, as well as the adoption of active teaching methodologies.
Keywords: student dropout vocational high school service dominant logic value co-creation